The Effect of Age and Gender on Consumption Decisions with Mental Accounting as an Intervening Variable - Baiq Davina Lolita Sari; Isnawati Isnawati (Cita konsultindo, 2024)
The purpose of this study was to examine the effect of age and gender on consumption decisions with mental accounting as an intervening variable conducted at the University of Mataram. the problem in this study is that people make consumption decisions without thinking long. This research is a development of previous research by adding new variables to be examined. The population in this study involved all students of the Faculty of Economics and Business, University of Mataram, class of 2017-2023, totaling 4,927 students. Based on calculations with the Slovin formula with an error rate of 10%, 97 results were rounded up to 100 students who were taken as samples. From the research that has been done, it is found that age and gender can influence a person's consumption decisions with mental accounting as an intervening variable. The results of this study can provide practical benefits for marketing policy planners, financial planners, and companies to develop more targeted strategies according to consumer demographic characteristics.